Health care dominants in Ukrainian proverbs and sayings (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
The article under consideration is devoted to Ukrainian proverbs and sayings from the point of their representation through the information about the reserving human health. The author proves that it is necessary to comprehend and aware about the folk wise during the development of society. It is claimed that proverbs and sayings are like a folk heritage. It helps a person, who choses it like a vital credo, to live life with the least amount of mistakes and discomfort, in complete harmony with both oneself and society. There are kept the main features of the Ukrainian mentality in Ukrainian proverbs and sayings.
Keywords: proverbs; sayings; folk wise; mentality